A descriptive study of the occurrence and significance of lipids in Taenia hydatigena eggs - Sánchez Thevenet, P. (2010)
The aim of this work was to investigate the lipid content of Taenia hydatigena eggs and to evaluate the role of lipids in the maintenance of embryo viability. The total lipid content of the egg was 4.5% (w/w). Five classes of neutral lipids were identified: esterified cholesterol, free cholesterol, triacylglycerols, diacylglycerols and free fatty acids. Our results suggest that triacylglycerols play a key role in the maintenance of embryo viability. In addition, we found that T. hydatigena eggs remain metabolically active by mobilisation of stored triacylglycerols. This study contributes to the understanding the survival strategies of a member of the Taeniidae family in the environment outside the host. © 2009 Elsevier B.V.